Desenvolvimento de compósitos poliméricos com metais atenuadores e estudo da eficiência de atenuação da radiação para aplicação em procedimentos radiológicos - Crissia Carem Paiva Fontainha (2016)
Poly(vinylidene-trifluorethylene) [P(VDF-TrFE)] polymer-based composites were developed by filling the polymer matrix with radiation attenuating metallic oxides in several concentrations, particularly the micro and nanosized bismuth and zirconium oxides, for application in medical radiology procedures. The P(VDF-TrFE)/ZrO2 composites were synthesized using pure and also yttrium stabilized ZrO2. In the synthesis route, some composites were filled with multiwalled carbon nanotubes (MWCNT) and functionalized with Methyl-Methacrylate acid (MMA). Othermetallic oxides with good attenuation properties were also tested. Composite characterization was performed by X-ray diffraction (DRX), infrared and ultraviolet-visible spectrometry (FTIR and UV-Vis), differential scanning calorimetry (DSC), scanning electron microscopy (SEM) andenergy dispersive X-ray spectrometry (EDS). The presence of surface-modifier, granulometry and metallic oxide concentration in the polymeric matrix were correlated to their influence in the miscibility, dispersion, crystallinity and degradation mechanisms during the synthesis process. The composites radio-degradation after exposure to high dose radiation was studied in order to evaluate their useful lifetime in radiology procedures. The experimental data revealed that a betterdispersion of the metallic oxide into the polymeric matrix is attained when using MMA surfacemodifier. The image quality preservation in radiology procedures was evaluated by using radiochromic films and image resolution standards objects. The X-ray attenuation measurementswere performed in the standard radiation conditions of the IEC 61267:2005, RQR2 (N40), RQR5 (N70) and RQR8 (N100), exposing the composites to 100 mGy, and evaluating the attenuated doses with radiochromic films. The composite attenuation properties were also investigated fo monoenergetic X-rays using Co, Cu, Mo and Ag tubes with photons with energy of 6.5 keV, 8.5 keV, 17.5 keV and 22.1 keV, respectively. The mass attenuation coefficients of P(VDFTrFE):Bi2O3 nanocomposites were evaluated to be higher than those of the microcomposites, in the energy range studied. The composites filled with 8% of ZrO2 presented attenuation factors around 20%, for the RQR5 reference radiation. For 6.5 keV monochromatic radiation, the attenuationfactors were estimated between 50% and 70% for the P(VDF-TrFE)/Bi2O3 micro and nanocomposites, respectively, for film thickness normalized to 0.5 mm.